2009
DOI: 10.1111/j.1365-3024.2009.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in resistance to mixed, predominantly Teladorsagia circumcincta nematode infections of sheep: from heritabilities to gene identification

Abstract: In cool temperate areas, such as Scotland, sheep are infected by a variety of nematodes but the dominant nematode is Teladorsagia circumcincta. Resistant animals have one or more of the following features: fewer adult nematodes, more inhibited larvae, shorter adult nematodes and decreased production of nematode eggs. In lambs at the end of the first grazing season, the heritability of adult worm length is very strong, whereas the heritability of egg production is moderate. The heritability of worm number is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 103 publications
3
66
0
Order By: Relevance
“…Moreover, we identified two SNPs (although below the suggestive significance level) on OAR 3 associated with IgA, which were also significant for FEC traits when analysed in ASReml. Although no causative mutation has been identified for these OAR3 QTL, the effect is often presumed to be mediated through INFG in sheep (Stear et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we identified two SNPs (although below the suggestive significance level) on OAR 3 associated with IgA, which were also significant for FEC traits when analysed in ASReml. Although no causative mutation has been identified for these OAR3 QTL, the effect is often presumed to be mediated through INFG in sheep (Stear et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Crawford et al, 2006) have failed to find any evidence on chromosome 3. Although no causative mutation has been identified for the FEC OAR3 QTL, the effect is often presumed to be mediated through INFG in sheep (Stear et al, 2009). Two QTL studies have reported an OAR14 FEC QTL, one in Blackface sheep (Davies et al, 2006) and the other in lactating Spanish milk sheep (Gutierrez-Gil et al, 2009), but the QTL positions were different in these two studies and neither study suggested any possible candidate genes underlying the QTL.…”
Section: Discussionmentioning
confidence: 96%
“…Random selection was achieved using a pseudorandom number generator to identify lamb IDs to be drenched. FEC measurements were assumed to be taken 5 days prior to treatment to allow time for the samples to be processed and analyzed, and included a 20% random sampling error (Bishop et al, 1996;Stear et al, 2009). LW was assumed to be measured the day prior to treatment.…”
Section: Simulation Procedures and In Silico Experimental Designmentioning
confidence: 99%